INTERPRETASI ANOMALI MEDAN MAGNET BUMI DI KAWASAN GUNUNGAPI LAMONGAN - Ninik Agustin (KURVATEK, 2020)
Lumajang is one of district at Jawa Timur regency where located Lamongan volcanic area. Lamongan volcano is a young monogenetic volcano that was growth from a fault at the summit. Eruption at Lamongan volcano not only occurred at the main volcano, but also at parasite cone at Lamongan volcanic area with 37 cinder cones dan 27 maars. Cinder cones dan maars formed from contact of magma and water that cause freatomagmatic eruption with pyroclastic debris and material deposit’s flow. This research focused at mapping western Lamongan volcanic area based on magnetic anomalies to conducted vulcanic activities at subsurface. Based on magnetic anomalies data, there is an area at south, west, and north with high temperature subsurface rock around maars and cinder cones, that is indicated by negative magnetic anomaly. Keywords: Lamongan volcano, maar, cinder cone, magnetic anomalies.